PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN PONOROGO - Rachmawati, Ruly; Rispantyo, Rispantyo; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims: 1) to analyze the significance of the influence of leadership style on employee performance in BKPPD Ponorogo Regency. 2) to analyze the significance of the influence of leadership style on work motivation in BKPPD Ponorogo Regency. 3) to analyze the significance of the effect of work motivation on employee performance in BKPPD Ponorogo Regency. 4) to analyze work motivation mediating the influence of leadership style on the performance of BKPPD Ponorogo Regency employees. The results of the research instrument show that indicators of leadership style, employee performance and work motivation indicators for validity testing are valid and invalid, for the results of the test of the relativity of leadership style, performance and motivation are reliable. The classical assumption test results show that the data are free of multicollinearity, free of autocorrelation, free of heteroscedasticity and normally distributed data. The sobel test results in this study indicate that motivation does not mediate the influence of leadership style on employee performance. Suggestions in this study employees are expected to increase employee motivation, especially staff, although these variables are not proven capable of mediating the influence of leadership style on performance